(untitled) (Revista Apotheke, 2021)
Beyond the pure formalism or stylism, erotic expressiveness in the field of art must be seen in a dialogism between the conception of the body and its socio-cultural circumstances. Whether synchronous, diachronic or anachronistic, any analysis of the visual manifestation of human sexuality is part of a negotiation (almost always asymmetrical) at the same time bioaesthetic and biopolitics for the (re)construction of identities. If art is a privileged field for the perception of divergent bodies and sexualities, it is necessary to peruse the ways in which these divergences became visible or invisible in the history of art cut in the interstice between modernity and contemporaneity. This is the primary purpose of this article. Therefore, the recurrence of authors such as Lou Andreas-Salomé, António Damásio, Didier Eribon, Michel Foucault, Dominique Fernandez and Judith Butler aims at the perception of various nuances in an unstable intermediation between male and female that, consequently, allows us to glimpse the existence (or not) of a peculiar queer erotic aesthetic.